2018
DOI: 10.1039/c8cc05692g
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective acyl-transfer catalysis by fluoride ions

Abstract: The asymmetric nucleophilic catalysis by fluoride ions at a carbon-based electrophile has been demonstrated for the first time. Using a library of ad hoc designed bifunctional phase-transfer catalysts in which both the anion and the cation are directly involved in the reaction, the desymmetrisation of meso-succinic and -glutaric anhydrides is possible. 19F NMR spectroscopic studies support the intermediacy of an acyl fluoride intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The synthesis and applications of bifunctional phase-transfer catalysts are very attractive to academies and industries for their high efficiency and environmental sustainability. [25][26][27][28][29] These Bif-PTCs usually contain both one quaternary onium salt center and at least one hydrogen-bonding donor group in their structures. The hydrogen-bonding donor groups include hydroxyl (-OH), (thio)urea and squaramide.…”
Section: The Preparation Of Bifunctional Phase-transfer Catalysts (Bimentioning
confidence: 99%
“…The synthesis and applications of bifunctional phase-transfer catalysts are very attractive to academies and industries for their high efficiency and environmental sustainability. [25][26][27][28][29] These Bif-PTCs usually contain both one quaternary onium salt center and at least one hydrogen-bonding donor group in their structures. The hydrogen-bonding donor groups include hydroxyl (-OH), (thio)urea and squaramide.…”
Section: The Preparation Of Bifunctional Phase-transfer Catalysts (Bimentioning
confidence: 99%
“…We recently demonstrated that ammonium fluorides equipped with hydrogen‐bond donating functionality ( e. g . 6 ) could promote the methanolic desymmetrisation of anhydrides such as 7 to yield hemiester 8 in excellent yield and 61 % ee (Figure B) via nucleophilic catalysis .…”
Section: Figurementioning
confidence: 99%
“…[12] In order to achieve high level of stereocontrol, the concentration of 1 must be kept low, as a (less enantioselective) pathway leading to 2 involving addition of the catalyst-derived enolate ion to another molecule of 1 (instead of a pseudo intramolecular acyl-transfer event to give 2 directly) was competitive. Evidence for this supposition was provided by the observation that an in situ-generated ammonium alkoxide derived from 4 underwent acylation to form 5 (presumably without turnover) in the presence of 1, yet the product 2 was generated in 85 % yield nonetheless ( Figure 1A).We recently [13] demonstrated that ammonium fluorides equipped with hydrogen-bond donating functionality (e. g. 6) could promote the methanolic desymmetrisation of anhydrides such as 7 to yield hemiester 8 in excellent yield and 61 % ee ( Figure 1B) via nucleophilic catalysis. [14,15,16] The intermediacy of acyl fluoride 6 a was proposed based on the formation and in situ detection (by 1 H NMR spectroscopic analysis) of an acyl fluoride intermediate (with subsequent confirmation of its catalytic competency) in an analogous reaction with an acyclic anhydride.Given the operationally complicating issues stemming from the acyl-transfer proclivities of phenolic carbonates experienced by Ooi et al, we postulated that fluoride catalysis of the Steglich rearrangement -which would generate considerably more electrophilic acyl fluorides -could be a promising avenue of investigation.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Numerous examples for utilization of acyl fluorides in synthetic organic chemistry have been reported [28], while recently, unique reactivity of acyl fluorides has been extensively disclosed due…”
Section: Introductionmentioning
confidence: 99%